2007
DOI: 10.1007/s10096-007-0391-4
|View full text |Cite
|
Sign up to set email alerts
|

PVL-positive MRSA in Austria

Abstract: The objective of this study was to present, for the first time, an overview of the existing Panton-Valentine leukocidin (PVL)-positive methicillin-resistant Staphylococcus aureus (MRSA) strains in Austria and to compare the situation with that found in other countries. Between 2001 and 2006 we analysed 1150 MRSA isolates - from infections as well as from colonisation - for the presence of PVL genes. The most common multilocus sequence types of the 94 PVL-positive MRSA strains were ST8, ST152, ST30, ST80, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 14 publications
3
21
2
Order By: Relevance
“…Surprisingly, we identified much higher rates of PVL-positive MRSA strains (28%) than the ones reported from other European countries (3 to 15%) (28,50) or from other Swiss urban areas (Basel, 1%; Zurich, 5%) (44,47). The only study recording high proportions (35%) of PVL-positive strains comes from Geneva (2002 to 2005), but it was performed with a highly selective collection of non-multidrug-resistant CA-MRSA strains (17).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Surprisingly, we identified much higher rates of PVL-positive MRSA strains (28%) than the ones reported from other European countries (3 to 15%) (28,50) or from other Swiss urban areas (Basel, 1%; Zurich, 5%) (44,47). The only study recording high proportions (35%) of PVL-positive strains comes from Geneva (2002 to 2005), but it was performed with a highly selective collection of non-multidrug-resistant CA-MRSA strains (17).…”
Section: Discussioncontrasting
confidence: 85%
“…Since 2004, LUKS has followed a search-and-destroy strategy (49,51), which has been successfully implemented in Northern and Western European countries with both low and high prevalences of MRSA (28,31,41) and in the United States (18). From January to June 2009, 4 index patients were discovered in our institution and 289 patients and health care staff members were screened for MRSA carriage, but no nosocomial transmission could be verified.…”
mentioning
confidence: 99%
“…This is an MRSA strain isolated from an abscess from a patient in Denmark in 2001 (7), and the data were deposited by Herminia de Lencastre. There are several reports in the literature linking ST152 with sporadic PVL-positive CA-MRSA infection in Central Europe (7,13,18,23,24,26), and a single sporadic MRSA ST152 isolate has been noted in Australia (3). However, to our knowledge, the current study is the first to record ST152 from an asymptomatic carriage isolate.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for the local predominance of this clone are unclear, but possibilities include adaptation to local abiotic (environmental) or biotic (host population) conditions, a competitive advantage against other clones, or localized transmission combined with low rates of migration. There is currently only one ST152 isolate in the MLST database, although a single locus variant of ST152 (ST377) (18). In sum, although the evidence from the literature suggests that ST152 is still relatively rare, it appears to be associated with PVL-positive CA-MRSA samples, and its distribution corresponds to a South-North belt stretching across the middle of Europe, from the Balkans through Slovenia, Austria, and Saxony.…”
Section: Discussionmentioning
confidence: 99%
“…The first ST152 clonal type was observed in a PVL-positive CA-MRSA isolate in Europe (Müller-Premru et al, 2005). In another study, ST152 was found to be the second most common (after ST8) clonal type among PVL-positive MRSA isolates in Austria (Krziwanek et al, 2007). In addition, Monecke et al (2007) reported a PVL-positive MRSA strain, isolated from an immigrant child from Macedonia, having ST152 clonal type and t355 spa type.…”
Section: Molecular Typing Of the Strainsmentioning
confidence: 97%